2021
DOI: 10.1088/1755-1315/752/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Response of Plutella xylostella (Lepidoptera: Yponomeutidae) Adults to Refugia Plant

Abstract: Selection of refugia plants is an important step when engineering the agroecological system. The refugia plants can be repellent or attractant to insect pests and in many species the role of each plant can be studied using the olfactory responses of the insect to volatile chemical cues emitted by the plant. The objective of this study was to determine the olfactory response of Plutella xylostella (Lepidoptera: Yponomeutidae) adults to several refugia plant candidates. Y-tube olfactometer tests were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The value of the Simpsons dominance index was highest in the Z.elegans and T. subulata treatment (0.92) and the lowest in the control treatment (0.87) (Table 2). It was indicated by the presence of refugia plants that can attract ants, one of which was reported by (Cruz et al, 2018;Leksono et al, 2019;Asmoro et al, 2021) reported that extrafloral nectar at the base of the leaves of T. subulata can attract various ants in the planting area.…”
Section: Resultsmentioning
confidence: 98%
“…The value of the Simpsons dominance index was highest in the Z.elegans and T. subulata treatment (0.92) and the lowest in the control treatment (0.87) (Table 2). It was indicated by the presence of refugia plants that can attract ants, one of which was reported by (Cruz et al, 2018;Leksono et al, 2019;Asmoro et al, 2021) reported that extrafloral nectar at the base of the leaves of T. subulata can attract various ants in the planting area.…”
Section: Resultsmentioning
confidence: 98%
“…Refugia plants and pest trap pestrepellent plants and attract natural enemies to live and reproduce in the area so that the presence of natural enemies can balance the pest population at a limit that is not detrimental (Asmoro and Winasa, 2021). This research is necessary because, based on previous research, sound can stimulate the encroachment of phosphorus nutrients and soil microbial populations (Munar et al, 2022) and is associated with decreasing pests (Qi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the hazardous effect of pesticides, such as their attractiveness and toxicity to bees, are still limited in Indonesia. Olfactometry is one of the assessment methods that can be used to evaluate the orientation responses to odor [22,23]. The attraction of bees to odor is the initial step in finding food sources (nectar and pollen).…”
Section: Introductionmentioning
confidence: 99%